IMPACT OF INTRAPRENEURIAL ORIENTATION, ENTREPRENEURIAL SKILLS AND PSYCHOLOGICAL EMPOWERMENT ON INTRAPRENEURIAL INTENTION OF HEIs IN KARACHI, PAKISTAN - Khan, Muhammad Rhies; Askari, Mahrukh; Laila, Anita; Ali, Qamber (Sampoerna University, 2022)
The dynamic business environment has dramatically changed the traditional business and organizational activities in every sector. Employees’ role in the fragile business environment is very important and had limitedly been evaluated. This research aims to evaluate the influence of individuals’ entrepreneurial orientation on intrapreneurial intention while evaluating the mediating roles of entrepreneurial skill and psychological empowerment among higher education institutions (HEIs) in Pakistan. A total of 230 valid questionnaires were received through cluster sampling followed by convenience sampling technique from HEIs of Karachi, Pakistan. The data received were analyzed through Smart-PLS to measure the structural model. This study attempted to evaluate the nexus between individual entrepreneurial orientation (risk, innovativeness, and proactivity) and intrapreneurial intention. The mediating role of psychological empowerment and entrepreneurial skill has also been evaluated. The findings revealed that both entrepreneurial skills and psychological empowerment partially mediate the relationship between individual entrepreneurial orientation and intrapreneurial intention and the direct effect before mediation was also significant. More importantly, risk and innovativeness are partially mediated by entrepreneurial skill while psychological empowerment did not. The proactivity is fully mediated by psychological empowerment, but others did not. The study implicates that individuals’ risk-taking, and innovativeness can be enhanced through their improved skills among members of HEIs. Moreover, psychological empowerment and freedom can enhance their proactivity.